Delimitative and Tentative Meaning in the Disposal 把 BA Construction - Vionita; Sutami, Hermina (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
There is much research done concerning the disposal 把 BA construction. Much of them examined why an object should be transposed to in front of the verb, and what kind of other elements behind the verb are. One of the other elements is verbal reduplication. Few researchers examine the meaning of verbal reduplication. The research aim is to guide the readers of Chinese texts on how to determine the meaning of verbal reduplication in 把 construction. Li & Thompson (1981), Zhuo Jing (2005) suggested delimitative and tentative meaning, and according to Wen (2017) “trial” is another meaning. The problem is how we can determine those meanings? The above researchers only give the verbal reduplication meaning from a sentence consisting of 把 construction. I used the above theory to ascertain which meaning is conveyed by considering co-text and context of 把 construction. The data was from 5 novels and 3 dramas from the situs www.millionbook.com, www.kanunu8.com, and www.juben68.com. The method done was considering the co-text and context where 把 construction appeared. The result obtained indicate that there is a combination of delimitative and tentative meaning in certain contexts. The novelty of this research is to guide the readers to ascertain which meaning is conveyed by verbal reduplication in 把 construction.